Exploring New Characteristics: Using Deep Learning and 3D Reconstruction to Compare the Original COVID-19 and Its Delta Variant Based on Chest CT - Bai, Na; Lin, Ruikai; Wang, Zhiwei; Cai, Shengyan; Huang, Jianliang; Su, Zhongrui; Yao, Yuanzhen; Wen, Fang; Li, Han; Huang, Yuxin; Zhao, Yi; Xia, Tao; et al. (Frontiers in Molecular Biosciences, 2022)
Purpose: Computer-aided diagnostic methods were used to compare the characteristics of the Original COVID-19 and its Delta Variant. Methods: This was a retrospective study. A deep learning segmentation model was applied to segment lungs and infections in CT. Three-dimensional (3D) reconstruction was used to create 3D models of the patient's lungs and infections. Proposed a stereoscopic segmentation method, which can subdivide the 3D lung into five lobes and 18 segments. An expert-based CT scoring system was improved and artificial intelligence was used to automatically score instead of visual score. Non-linear regression and quantitative analysis were used to analyze the dynamic changes in the percentages of infection (POI). Results: The percentages of infection in the five lung lobes of all patients were calculated and converted into CT scores. The CT scores of Original COVID-19 patients and Delta Variant patients since the onset of initial symptoms were fitted over time, respectively. The peak was found to occur on day 11 in Original COVID-19 patients and on day 15 in Delta Variant patients. The time course of lung changes in CT of Delta Variant patients was redetermined as early stage (0-3 days), progressive and peak stage (4-16 days), and absorption stage (17-42 days). The first RT-PCR negative time in Original COVID-19 patients appeared earlier than in Delta Variant patients (22[17-30] vs 39[31-44], P<0.001). Delta Variant patients had more re-detectable positive RT-PCR test results than Original COVID-19 patients after the first negative RT-PCR time (30.5% vs 17.1%). In the early stage, CT scores in the right lower lobe were significantly different (Delta Variant vs Original COVID-19, 0.8±0.6 vs 1.3±0.6, P=0.039). And in the absorption stage, CT scores of the right middle lobes were significantly different (Delta Variant vs Original COVID-19, 0.6±0.7 vs 0.3±0.4, P=0.012). The left and the right lower lobes contributed most to lung involvement at any given time. Conclusion: Compared with Original COVID-19, Delta Variant has a longer lung change duration, the peak of infection occurred later, more re-detectable positive RT-PCR test results, different locations of pneumonia, and more lesions in the early stage, etc.